Evaluation of excreta management in a large French multi-hospital institution. Issue 4 (December 2015) - Lepainteur, M.; Nérome, S.; Bendjelloul, G.; Monteil, C.; Cottard-Boulle, B.; Nion-Huang, M.; Jarlier, V.; Fournier, S.
Summary: Background: Excreta are a major source of multidrug-resistant Enterobacteriaceae including strains that produce extended-spectrum beta-lactamase (ESBL). The increase of ESBL incidence in Assistance Publique – Hôpitaux de Paris (AP-HP) hospitals prompted an evaluation of the equipment and practices used to dispose of excreta. Aim: To evaluate the use of equipment for the management of excreta and to review practices of healthcare workers in their disposal. Methods: A cross-sectional survey was conducted in 2012. Findings: A total of 28 AP-HP hospitals including 536 units (342 acute care units and 194 rehabilitation and long-term care units) were evaluated. Among the patients on the day of the survey, 5697 (43%) wore diapers and 1767 (13%) were using a bedpan. Sixty-one percent of the beds were equipped with shared toilets and 43% of the toilets were equipped with hand sprayers, a device favouring the spread of faecal material in the environment. Sixty eight percent of the units were equipped with bedpan washer-disinfectors. Only 52% of the bedpan washer-disinfectors were located in rooms where alcohol-based hand rubs (ABHRs) were available. In 71% of the units the bedpan was rinsed before disinfection, mostly in the patient's bathroom (62%). Finally, only 9% of questioned healthcare workers said they followed an educational programme about excreta disposal. Conclusion: This survey shows that, in the field of multidrug-resistant Enterobacteriaceae control and the promotion of hand hygiene with ABHRs, excreta management is a concerning but neglected subject.